Does Early Environmental Complexity Influence Tyrosine Hydroxylase in the Chicken Hippocampus and “Prefrontal” Caudolateral Nidopallium? - Tahamtani, Fernanda M.; Nordgreen, Janicke; Brantsæter, Margrethe; Østby, Gunn C.; Nordquist, Rebecca E.; Janczak, Andrew M. (Frontiers in Veterinary Science, 2016)
In adult chickens, the housing system influences hippocampal morphology and neurochemistry. However, no work has been done investigating the effects of the early life environment on chicken brain development. In the present study, we reared 67 commercial laying hens (Gallus gallus domesticus) in two environments that differed in the degree of complexity (aviary or cage system). These two groups were further divided into two age groups. At 20 weeks of age 18 aviary-reared birds and 15 cage-reared birds were humanely euthanized and their brains dissected. At 24 weeks of age, a further 16 brains from aviary-reared birds and 18 brains from cage-reared birds were collected. These brains were prepared for immunohistochemical detection of tyrosine hydroxylase (TH), the rate-limiting enzyme in the biosynthesis of dopamine, in the hippocampus and the caudolateral nidopallium (NCL). There were no differences between the treatment groups in TH staining intensity in the hippocampus or the NCL. In the medial hippocampus, the right hemisphere had higher TH staining intensity compared to the left hemisphere. The opposite was true for the NCL, with the left hemisphere being more strongly stained compared to the right hemisphere. The present study supports the notion that the hippocampus is functionally lateralized, and our findings add to the body of knowledge on adult neural plasticity of the avian brain.